The Ophiuchus Disk Survey Employing Alma (Odisea): Complete Size Distributions for the 100 Brightest Disks Across Multiplicity and Spectral Energy Distribution Classes - Rannou-Fuentes, F; Perez-Marquez, S; Miley, J; Gonzalez-Ruilova, C (American Astronomical Society, 2025)
The size of a protoplanetary disk is a fundamental property, yet most remain unresolved, even in nearby star-forming regions (d ∼ 140-200 pc). We present the complete continuum size distribution for the 105 brightest protoplanetary disks (Mdust ≳ 2 M⊕) in the Ophiuchus cloud, obtained from ALMA Band 8 (410 GHz) observations at 0 . ″ 05 (7 au) to 0 . ″ 15 (21 au) resolution. This sample includes 54 Class II and 51 Class I and flat-spectrum sources, providing a comprehensive distribution across evolutionary stages. We measure the half-width at half-maximum and the radius encircling 68% of the flux (R68%) for most nonbinary disks, yielding the largest flux-limited sample of resolved disks in any star-forming region. The distribution is log-normal with a median value of ∼14 au and a logarithmic standard deviation σ log = 0.46 (factor of 2.9 in linear scale). Disks in close-binary systems (<200 au separation) have smaller radii, with a median value of ∼5 au, indicating efficient radial drift as predicted by dust evolution models. The size distribution for young embedded objects (spectral energy distribution Class I and flat spectrum, age ≲1 Myr) is similar to that of Class II objects (age ∼ a few Myr), implying that pressure bumps must be common at early disk stages to prevent millimeter-sized particle migration at astronomical unit scales. © 2025. The Author(s). Published by the American Astronomical Society.